2015
DOI: 10.3168/jds.2015-9856
|View full text |Cite
|
Sign up to set email alerts
|

Partial calcium depletion during membrane filtration affects gelation of reconstituted milk protein concentrates

Abstract: Milk protein concentrate powders (MPC) with improved rehydration properties are often manufactured using processing steps, such as acidification and high-pressure processing, and with addition of other ingredients, such as sodium chloride, during their production. These steps are known to increase the amount of serum caseins or modify the mineral equilibrium, hence improving solubility of the retentates. The processing functionality of the micelles may be affected. The aim of this study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The interstudy discrepancy may be related to differences in the concentrations of Ca, P, and [Ca 2+ ] and pH at rennet gelation. The use of cold UF-DF (10°C) by Martin et al (2010), compared with warm UF-DF (50°C) in the current study, is likely to have depleted the concentration of [Ca 2+ ] and CCP in the MPC (Brule and Fauquant, 1981;Law and Leaver, 1998;Eshpari et al, 2015). Hence, Martin et al (2010) found that the addition of CaCl 2 at concentrations of 2 to 3 mM to the aqueous-based MPC restored rennet-induced gelation.…”
Section: Rennet Gelation Of Protein Dispersionsmentioning
confidence: 71%
See 1 more Smart Citation
“…The interstudy discrepancy may be related to differences in the concentrations of Ca, P, and [Ca 2+ ] and pH at rennet gelation. The use of cold UF-DF (10°C) by Martin et al (2010), compared with warm UF-DF (50°C) in the current study, is likely to have depleted the concentration of [Ca 2+ ] and CCP in the MPC (Brule and Fauquant, 1981;Law and Leaver, 1998;Eshpari et al, 2015). Hence, Martin et al (2010) found that the addition of CaCl 2 at concentrations of 2 to 3 mM to the aqueous-based MPC restored rennet-induced gelation.…”
Section: Rennet Gelation Of Protein Dispersionsmentioning
confidence: 71%
“…There are 2 types of HCT versus pH profiles for bovine milk: type A, which is the most common and is characterized by a maximum HCT at pH 6.6 to 6.7 and a minimum HCT at pH 6.8 to 7.0, and type B, for which HCT increases progressively with pH increases in the range of 6.2 to 7.2 (O'Connell and Fox, 2003). Eshpari et al (2015Eshpari et al ( , 2017 altered the solvent composition of protein dispersions (3.2% protein) prepared from standard-or reduced-Ca MPC with protein content ≥80% by overnight dialysis against skim milk at 4°C. The pH of the nondialyzed standard-Ca and reduced-Ca samples was 7.1 and 6.68, respectively, whereas that of the corresponding dialyzed standard-Ca and reduced-Ca samples was 6.65 and 6.65, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…; Dalgleish and Corredig ; Eshpari et al . ). However, earlier analysis (results not shown) revealed that this mainly affects soluble calcium, and thus CM do not disintegrate (Kulozik ).…”
Section: Methodsmentioning
confidence: 97%
“…Acidification of skim milk before ultrafiltration, addition of monovalent cations or calcium chelators, and injection with CO2 have been used to reduce the Ca content of MPC. A decrease in the pH of skim milk during UF was reported to affect the integrity and supramolecular structure of casein micelles due to the partial removal of Ca [44,45] and the internal structure of the nondissociated micelles became more homogenous. Replacement ~ 30% of Ca with Na in MPC powder was carried by contacting an aqueous solution of MPC with a strong cation ion exchanger in the sodium form [46].…”
Section: 1reducing Calcium Content Of Mpcsmentioning
confidence: 99%